211 Greenhouse Gas Emissions from Two Beef Systems from Birth to Slaughter in Eastern Nebraska. (12th April 2022) - McPhillips, Levi J; Carlson, Zachary; MacDonald, Jim C; Suyker, Andy; Awada, Tala; Watson, Andrea K; Okalebo, Jane; Xiong, Yijie; Dangal, Shree; Heil, Holly A; Stowell, Rick; Erickson, Galen E
Abstract: Greenhouse gas emissions from a conventional (CONV) pasture-based cattle production system with cows wintered on corn residue and summer grazing of brome pasture was compared with partial-confinement system (ALT) with cows and calves in a drylot during the summer and grazed cover crops and corn residue over the fall and winter. Four groups of 20 cows were in each system. Eddy covariance methods were used to measure emissions from grazed areas (corn residue and pasture) and pen chambers were used to measure emissions from feedlot pens (cows and calves). Cattle from the CONV system produced more CH4 and CO2 but produced more beef per cow exposed (321 and 303 kg HCW for CONV and ALT, respectively). Measured CH4 and modeled N2 O emissions totaled 7.5 ± 0.3 and 7.4 ± 0.3 kg CO2 e kg -1 HCW for CONV and ALT production, respectively. There was a measured uptake of 233 g C m -2 and 98 g C m -2 from brome pasture and cover crop, respectively. Accounting for CH4 and N2 O emissions using global warming potential (GWP) of 23 and 298 resulted in a net sink of 0.7 ± 0.2 kg CO2 e kg -1 HCW for CONV and source of 16.7 ± 1.5 kg CO2 e kg -1 HCW for ALT. The same calculation using global warming potential (GWP) of 4 and 234 resulted in a net sink of 10.9 ± 1.0 kg CO2 e kg -1 HCW for CONV and source of 7.1 ± 1.5 kg CO2 e kg -1 HCW for ALT. Carbon sequestration from perennial grasslands in the CONV was enough to offset all emissions and biogenic CO2 and the annual forage grazed in the ALT system offset 33 to 72% of systems emissions depending on GWP metric used.